Cavity optomagnonics - Viola Kusminskiy, Silvia (Optomagnonic Structures: Novel Architectures For Simultaneous Control Of Light And Spin Waves, 2021)
In the recent years a series of experimental and theoretical efforts have centered around a new topic: the coherent, cavity-enhanced interaction between optical photons and solid state magnons. The resulting emerging field of Cavity Optomagnonics is of interest both at a fundamental level, providing a new platform to study light-matter interaction in confined structures, as well as for its possible relevance for hybrid quantum technologies. In this chapter, I introduce the basic concepts of Cavity Optomagnonics and review some theoretical developments.
CRIS-Team Scopus Importer:2021-07-16